Kewarisan Anak Hasil Sewa Rahim di Indonesia Ditinjau dari Aspek Nasab - Ulum, Mukhamad Bahrul (LPPM Universitas Ekasakti Padang, 2023)
The purpose of this research is to know the inheritance of children from uterine leasing in Indonesia from the perspective of nasab. The method used in this research is normative juridical method. The data used is secondary data in the form of law books, scientific journals, and laws and regulations related to the topic of discussion. This research is descriptive analytical. This research uses the Ta'lily approach. While the theory used is the theory of inheritance (nasab). The results of the study indicate that the civil relationship is owned by the child from the results of renting a uterus with a surrogate mother. So, those who can inherit each other are the child and the surrogate mother, if the surrogate mother is bound by a legal marriage, her husband also has a link to the inheritance of the child she gave birth to. If the husband and wife who gave the fetus want to inherit the child from uterine leasing, it is necessary to use inheritance or a will with testamentair.